Achromatic metalens for thermal imaging - Lim, Bryan Zhi Wei (Nanyang Technological University, 2023)
Controlling light at the nanoscale level is a cutting-edge technology, and metalenses are at the forefront of this field. Composed of an array of structures that manipulate the phase and amplitude of light, metalenses are extremely thin and flat, offering many advantages over traditional lenses. However, despite these benefits, metalenses are still subject to certain limitations, such as their narrow field of view (FOV), which makes them less suitable for large FOV imaging applications. This report focuses on designing and simulating a metalens with a large FOV.